THE INVESTIGATION OF 2013 CURRICULUM IN ENGLISH TEACHING PROCESS AT SMA MUHAMMADIYAH 1 PONOROGO - Sauqi Hadi Permono; Ana Maghfiroh; Diyah Atiek Mustikawati (EDUPEDIA, 2019)
2013 Curriculum considered as new curriculum in Indonesia. In this curriculum, students demanded to be active and creative during learning process. Thus, teacher also needs to be creative in arranging the teaching and learning process. This research aims at finding out (1) the teachers’ implementation of 2012 curriculum in English teaching process; (2) the teachers’ and students roles in English teaching and learning; and (3) the impact of 2013 curriculum in English teaching and learning. This research design was descriptive qualitative research. The researcher used qualitative observation and interview as the data collection technique. The subject were three English teachers of SMA Muhammadiyah 1 Ponorogo. The activity in analyzing data were reduction, display, and conclusion drawing or verification. The findings of the research showed that the implementation of 2013 curriculum in English teaching process did not completely successful. It showed from the data findings, there were positive and negative impact of the 2013 curriculum implementation in English teaching process at SMA Muhammadiyah 1 Ponorogo. The creativity of English teacher in arranging learning activities will create a good learning situation and increase the students understanding towards the learning material.